2005
DOI: 10.1029/2004jd005332
|View full text |Cite
|
Sign up to set email alerts
|

Cloud‐to‐ground lightning in Austria: A 10‐year study using data from a lightning location system

Abstract: [1] In this paper we present lightning statistics for more than three million cloud-toground (CG) flashes located during the 10-year operation period 1992-2001 of the Austrian lightning location system (LLS) called ALDIS (Austrian Lightning Detection and Information System). Like a majority of other LLS operated worldwide, ALDIS underwent configuration changes and continuous performance improvement. Since these changes can alter the lightning statistics, we also relate the variation of the individual lightning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
123
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(146 citation statements)
references
References 32 publications
16
123
1
6
Order By: Relevance
“…The median values (60 ms) was essentially the same in both locations. This value is also the same that observed by Schulz et al [28] in Austria in a 1O-year study using data from a high detection efficiency lightning location system. Many other authors have reported median values of inter stroke intervals around 60 ms [e.g., 6,17,29,30].…”
Section: Flash Multiplicity Interstroke Interval and Number Of supporting
confidence: 77%
“…The median values (60 ms) was essentially the same in both locations. This value is also the same that observed by Schulz et al [28] in Austria in a 1O-year study using data from a high detection efficiency lightning location system. Many other authors have reported median values of inter stroke intervals around 60 ms [e.g., 6,17,29,30].…”
Section: Flash Multiplicity Interstroke Interval and Number Of supporting
confidence: 77%
“…Both values are lower than reported in most lightning climatology studies around the world (and see Table 1). This may be explained by the dominance of winter thunderstorms in the Eastern Mediterranean, which have different characteristics than summer or tropical convective storms that are most studied globally (Cummins et al, 1998b;Schulz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Cummins et al (1998), positive flashes with peak current lower than 10 kA should be regarded as cloud discharges. However, some other researchers pointed out that "the limit of 10 kA is somewhat arbitrary, and may be related to network configuration and climate" (Schulz et al, 2005). When the weak positive strokes (b10 kA) were removed from the dataset, the average peak current for positive strokes was from 15.2 to 20.7 kA as shown in Table S1 in the Supplementary material.…”
Section: Lightning Characteristics During Active Lightning Seasons Ovmentioning
confidence: 94%